Wheeleriola perplexa gen. et sp. nov., the first member of Catotrichinae (Diptera: Cecidomyiidae) found in New Zealand - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2020)
Catotrichinae, a small, relict subfamily of the Cecidomyiidae, are of peculiar interest to the phylogeny of gall midges. Three genera and eight species of extant catotrichines were previously known to science, all found in the Holarctic region and Australia. Here, the first New Zealand member of this group is described and named Wheeleriola perplexa, new genus, new species. The adult morphology of Wheeleriola is characterized by two peculiarities: the vestiture on the male flagellomeres shows beginnings of girdle formation, and the medial veins are largely reduced. Both conditions challenge the hypothesis of Catotrichinae being the earliest branching lineage of the cecidomyiid clade, which is explained and discussed.